Pengembangan E-Modul Berbasis PMRI pada Materi Segi Empat Kelas VII SMP - Febriana, Suci; Refianti, Rani; Luthfiana, Maria (Jurnal Pendidikan Matematika : Judika Education, 2023)
This study aims to develop an PMRI-based e-module product on rectangular class VII class VII SMP IT AN-NIDA Lubuklinggau according to the 2013 curriculum and to produce e-modules that are valid, practical and have potential effects. This development research method uses the ADDIE development model (Analysis-Design-Develop-Implement-Evaluate). The research was conducted at SMP IT AN-NIDA Lubuklinngau so that the population and sample or research subjects were class VII students with a total of 28 students. Data collection techniques in this study used interviews, questionnaires and tests. The data analysis technique uses the validity of linguists with a value of 0.75, media experts with a value of 0.72 and material experts with a value of 0.68, so that the results of the analysis of the three validators get a value of 0.71 in the valid category. Furthermore, the practicality analysis of teachers and students gets a score of 92.07% in the very practical category and has a potential effect of 92.85%. So it can be concluded that the PMRI-based e-module on rectangular class VII class VII SMP IT AN-NIDA Lubuklinggau has met the criteria of being valid, practical and has a potential effect. Keywords: e-module, PMRI, Quadrilatera